A historical analysis and the identification of driving forces behind the evolution of the urban macro skyline of Shiraz, Iran. Issue 4 (10th June 2020) - Mohseni, Farnaz; Weidner, Silke; Kloos, Michael
Abstract : Purpose: The historic city of Shiraz, in the south of Iran, is renowned for its monuments and its remarkable macro skyline, which has been destructively affected by the rapid urban development. This research proposes a systematic historical analysis, which can discover the driving forces behind the evolution of the macro skyline of Shiraz, in the past as well as contemporary times. Design/methodology/approach: The proposed general framework of the methodology is constituted of systematic historical mapping and documentation, which is based on a desk study and field research. Moreover, by means of this methodology, different layers and driving forces of shaping the urban macro skyline are extracted. Findings: The outcome demonstrates 12 driving forces or contributing factors behind the evolution of the urban macro skyline. Based on the results, it is concluded that there was a shift in the subject and content of driving forces during the last century that has contributed to the destructive effects on the silhouette of Shiraz in turn. Practical implications: It is suggested that the proposed comprehensive method, which is based on the historical analysis and the field survey, can be applied as a documentation platform. It is believed that the analysis and the extraction of driving forces can facilitate future urban landscape management plans as well as possible impact assessments. Originality/value: Many studies rely on the analysis of historical data in landscape assessment. Nevertheless, this research develops an innovative historical analysis, which identifies the driving forces behind the evolution of the urban macro skyline over time.